Typification of two species names in Dendrochilum (Orchidaceae, subgenus Platyclinis) - Naive, Mark Arcebal K.; Sanders, Trey (Phytotaxa, 2020)
Dendrochilum Blume (1825: 593), as currently circumscribed, comprises approximately 290 species distributed in Southeast Asia (Pedersen et al. 2019). In the course of updating the genus Dendrochilum website (https://www.dendrochilum.com) and as a start of our revisionary work on the genus, we came across two species names that warrant lectotypification in accordance with the Shenzhen code Art. 9.3, 9.11, 9.12 (Turland et al. 2018). This is accomplished below.